Intravenous dexmedetomidine versus propofol for intraoperative moderate sedation during spinal anesthesia: A comparative study - Pratibha Jain Shah; Kamta Prasad Dubey; Kamal Kishore Sahare; Amit Agrawal (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: There has been a paradigm shift of focus toward quality of spinal anesthesia with sedation being an integral aspect of this regional anesthesia technique. Thus, this study was designed to compare efficacy of intravenous dexmedetomidine and propofol for moderate sedation during spinal anesthesia. Material and Methods: A total of 120 patients of age group 18-60 years of American Society of Anesthesiologists grade I & II, posted for surgeries under spinal anesthesia were randomly divided in to three groups (n = 40 each); Group D received infusion of dexmedetomidine 1 μg/kg over 10 min followed by maintenance infusion of 0.5 μg/kg/h. Group P received infusion of propofol 6 mg/kg/h for 10 min followed by the infusion maintenance of 2.5 mg/kg/h. Group C (control group) received normal saline. Level of sedation (using observer's assessment of alertness/sedation score), pain intensity (by visual analogue scale), onset and recovery from sedation, hemodynamic changes, and overall patient's satisfaction were assessed. Results: The onset and recovery from sedation were significantly earlier with propofol (15.57 ± 1.89 min vs. 27.06 ± 2.26 min; P < 0.001) however intraoperative sedation (level 4), and overall patient's satisfaction was significantly better with dexmedetomidine group (p < 0.05). Duration of postoperative analgesia was significantly prolonged with dexmedetomidine (225.53 ± 5.61 min vs. 139.60 ± 3.03 min; P = 0.0013). Mean heart rate and blood pressure were significantly lower in the propofol group (P < 0.05). Conclusion: Dexmedetomidine with its stable cardio-respiratory profile, better sedation, overall patient's satisfaction, and analgesia could be a valuable adjunct for intraoperative sedation during spinal anesthesia.